A Tipologi Kesetaraan Gender Dalam Pernikahan Islam (Studi Penafsiran Hamka Tentang Ayat-ayat Hak dan Kewajiban Suami Istri Dalam Tafsir al-Azhar).: Typology of Gender Equality in Islamic Marriage (Study of Hamka's interpretation About the Verses of the Qur'an of Rights and Obligations Husband and Wife in Al-Azhar’s interpretation) - Malihatus Syafiyah Syafiyah (el-Bait: Jurnal Hukum Keluarga Islam, 2022)
Abstract Typology of Gender Equality in Islamic Marriage (Study of Hamka's interpretation About the Verses of the Qur'an of Rights and Obligations Husband and Wife in Al-Azhar’s interpretation) Tesis: Hamka is a multi-dimensional figure who has not studied formal education, but Hamka is able to master almost all kinds of science. Tafsir al-Azhar is a monumental book of Hamka that appears with a more objective interpretation in discussing the problems of women and men. Hamka tries to shift the feminist thinking that assesses the commentators are always dominant in interpretations that seem to marginalize women. In addition, Hamka is a figure who cares about women. He also talked a lot about justice. it is the reasson of the writer to reseach Tafsir Hamka. The purposes of this study was to answer the research problems, are 1) what is the typology of Hamka's interpretation in Tafsir al-Azhar ? 2) how are the rights and obligations of husband and wife according to Hamka's interpretation in Tafsir al-Azhar? 3) how the relevance of the interpretation of Hamka with feminism? In this research, qualitative research with inductive deductive method with gender approach is used. The collection used documentation method. Data analysis uses data reduction flow, data presentation, and conclusion drawing. The validity of the data uses triangulation and in-depth observation. The results of this study are: 1) Hamka's interpretation in Tafsir al-Azhar is included in the typology of modernist quasi-objective interpretation with consideration; a) attachment to conventional values ​​but b) use of social theory in the interpretation verse of the Qur'an. 2) The interpretation of Hamka related rights and obligations of husband and wife are egalitarian-emancipatory well as in line with the principal of gender namely the theory of functionalist structuralis. In this case Hamka makes the rights and roles of women in the household as a comparison of the rights and roles of men as leaders of the household. It is emansitive because in its interpretation efforts Hamka is more advanced by including immaterial rights. Theory of functionalist structuralis seeks to explain how the system was always functioning to obliged balance in the institution of the family. 3) While the relevance of Hamka's interpretation of feminism is included in the thought of moderate feminism with consideration; a) the combination of old values ​​with new values ​​b) rejecting patriarchal tradition c) textual and contextual elaboration. Keywords: Tipologi Kesetaraan Gender, Pernikahan Islam, Hak dan Kewajiban, Tafsir al-Azhar